School Choice, Student Sorting, and Academic Performance - Munteanu, Andrei (The Review of Economics and Statistics, 2026)
Abstract This study examines the impact of school choice on academic achievement. I use differences in the number of schools across similar Romanian towns, generating variation in school choice for local students, who compete for seats via test scores. I find that more school choice results in increased sorting of students by admission scores across different schools. Sorting widens achievement gaps between high- and low-admission score students. High-scorers having access to better teachers and peer effects are the primary factors explaining these widening gaps. Last, between-school competition via school choice does not increase average achievement levels.